IMPLEMENTATION OF THE PRINCIPLE OF THE BEST INTEREST OF THE CHILD IN THE JUVENILE CRIMINAL JUSTICE SYSTEM: A CASE STUDY IN THE MERAUKE DISTRICT COURT - Rendie Meita Sarie Putri; Nurul Widhanita Y. Badilla; Riez Kifli Kolewora; Ros Amira bt Mohd Ruslan (Faculty of Law Sriwijaya University, 2026)
Children in conflict with the law require special protection within the juvenile criminal justice system to ensure the fulfillment of their rights and interests. This study examines the implementation of the principle of the best interests of the child in the juvenile criminal justice system, particularly through the diversion mechanism as regulated under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The research aims to analyze the application of this principle and identify obstacles that may hinder its effective implementation. This study employs a normative juridical method using statutory, conceptual, and case approaches. Legal materials were collected through literature review and analyzed qualitatively. The results indicate that the principle of the best interests of the child is reflected in the diversion process, which prioritizes restorative justice, rehabilitation, and the protection of children’s rights while maintaining consideration for victims’ interests. However, several challenges remain, including the dependence on victim consent in diversion proceedings, limited public understanding of restorative justice, low community participation, and the need for stronger institutional support in implementing diversion. Therefore, enhancing public awareness, strengthening stakeholder involvement, and improving diversion guidelines are necessary to ensure that the best interests of the child are consistently realized within the juvenile criminal justice system.